Effectiveness of the Religious Harmony Guidance Program in West Java - Luthfi Anwar Mahbubi (Zona Law And Public Administration Indonesia, 2023)
The religious harmony guidance program carried out by the Legal and Religious Subdivision of the Regional Office of the Ministry of Religion of West Java Province is intended to create peace and harmonious relations between religious communities. Ironically, the research of the religious harmony index by the Ministry of Religion in 2019 shows that West Java ranks third with the lowest score in Indonesia. The purpose of this study was to determine the effectiveness implementation of religious harmony guidance program for Religious Affairs and Religious Affairs Subdivision Regional Office of the Ministry of Religion of West Java. This study uses the Nugroho Policy Effectiveness theory with five precise indicators, namely: 1) right policy; 2) proper implementers; 3) right on target; 4) appropriate environment; and 5) proper process. This research uses a qualitative approach with a descriptive method to address the issues examined by collecting data through observations, interviews, and documentation. The results of this study indicate that the implementation of religious harmony guidance program Legal Subdivision and Religious Harmony The Regional Office of the Ministry of Religion of West Java Province has not all been effective based on the five right policies, namely the right policies, implementers, the right target, the right environment, and the right process.